Problem Based Learning Model with the TPACK Approach in the Numeracy Ability of Fifth Grade Elementary School Students - Sayu Rahma Indriani; Gusti Ngurah Sastra Agustika (Jurnal Pedagogi dan Pembelajaran, 2023)
The 2018 PISA results, Indonesian Education Report Card Data, and AKM Scores show that the numeracy skills of fifth-grade elementary school students in Indonesia still need to improve. One of the contributing factors is the dominance of the use of the lecture method in the learning process. This research analyzes the Problem-Based Learning Model with the TPACK Approach in the Numeracy Ability of Class V Elementary School Students. This research is an experimental research with a Nonequivalent Pretest post-test control Group Design. This research was conducted on fifth-grade elementary school students who were divided into an experimental group and a control group determined using the Cluster Random Sampling Technique. Data from this research was collected using a test method using a numeracy ability test instrument. Data were analyzed using the Polled Variance T-test because it has a homogeneous data variance. The results of this research show a significant difference in numeracy abilities in students who are taught using the Problem-Based Learning model with the TPACK Approach and in students who are not taught using this model. The Problem-Based Learning model with the TPACK approach can be used in the learning process, especially numeracy learning because this model can encourage students to learn independently so that students can discover and understand concepts through themselves.